Isotopologue consistency of semi-empirically computed infrared line lists and further improvement for rare isotopologues: CO2 and SO2 case studies. (June 2019) - Huang, Xinchuan; Schwenke, David W.; Lee, Timothy J.
Highlights: For line intensity: Systematic investigation on the isotopologue consistency of CO2 and SO2 IR/MW intensity. Interesting TDM/Einstein-A patterns found for CO2 vibrational polyads, SO2 and CO2 MW, fundamentals, hotbands, etc. For line positions: First 2nd-round implementation of BTRHE strategy to minimize the isotope/mass dependent residuals. –– Two orders of magnitude improvement for SO2 MW prediction accuracy: 0.01-0.02 MHz (A/B/C), 0-5 MHz (J/Ka<20 lines). This approach starts from and targets at higher accuracy, can easily extend to other bands or molecules. Abstract: The semi-empirical molecular rovibrational IR line lists, such as ExoMol, TheoReTs, and Ames, combine the experimental accuracy and theoretical power to reach better than 0.1 cm −1 accuracy for line positions and better than 80–90% agreement for line intensities. The quality of these existing semi-empirical IR lists allows further improvements of intensity and line positions for those unobserved minor isotopologues. This paper presents our new BTRHE (Best Theory + Reliable High-resolution Experiment) strategy implementation. For line intensity, the isotopologue consistency and the patterns of mass dependence in the Ames-296 K SO2 and CO2 IR lists are quantitatively presented along the mass-inverse coordinates. The consistency and patterns are better than those in existing experimental data. The methodology proposed here can be used to identify inconsistencies, outliers, and mistakes in intensities, and help improve Effective Dipole Model (EDM) and molecular IR databases. We call for an experimental study on the 50006 and 60007 bands of CO2 628. For line position predictions, a simple approach combining the variational IR line lists with Effective Hamiltonian (EH) model may refine the effective rotational constants A0 /B0 /C 0 and quartic centrifugal distortion constants of minor isotopologues. The prediction accuracy may be improved by two orders of magnitude, i.e. reaching 0–5 MHz prediction accuracy in the range of J  < 20–30, Ka  < 10–20, and 0.01–0.02 MHz accuracy for A0 /B0 /C 0 . Several important factors have been systematically investigated and discussed, e.g. convergence, uncertainties, higher order terms, fixing EH parameters, mass coordinates, etc. A microwave (MW) line set consisting of 644, 636 strong transitions (at 296K) for all 30 isotopologues and corresponding refined EH(Ames) parameters are reported in the supplementary material. This approach may be easily extended to rovibrational bands, hot bands, and other molecular systems.